2018
DOI: 10.1002/jlcr.3633
|View full text |Cite
|
Sign up to set email alerts
|

New trends and applications in carboxylation for isotope chemistry

Abstract: Carboxylations are an important method for the incorporation of isotopically labeled 14CO2 into molecules. This manuscript will review labeled carboxylations since 2010 and will present a perspective on the potential of recent unlabeled methodology for labeled carboxylations. The perspective portion of the manuscript is broken into 3 major sections based on product type, arylcarboxylic acids, benzylcarboxylic acids, and alkyl carboxylic acids, and each of those sections is further subdivided by substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
0
22
0
3
Order By: Relevance
“…Although FMDS method had been used to generate a variety of nucleophiles in many organic reactions (such as alkylation, allylation, alkynylation, arylation, vinylation, and cyanation), and had been broadly used to synthesize complex molecules 11 , there are only a handful of reports of directly using organosilanes for carboxylation reaction without involving any transition metal catalysts [19][20][21][22][23][24][25][26][27][28][29] . While organometallic reagent catalyzed carboxylation has already drawn extensive attention to radiochemistry research [30][31][32] , to the best of our knowledge, we have not found any reports of the use of the FMDS methodology for direct 11 Ccarboxylation. It is comprehensible that the high cost and necessity of stoichiometric amounts of organosilane reagents made this method less attractive in synthetic organic chemistry research when compared to other organometallic reagent catalyzed carboxylation methodologies 33,34 .…”
Section: Synthesis Of [ 11 C]acetoacetic Acid Via Fmds 11 C-carboxylamentioning
confidence: 98%
“…Although FMDS method had been used to generate a variety of nucleophiles in many organic reactions (such as alkylation, allylation, alkynylation, arylation, vinylation, and cyanation), and had been broadly used to synthesize complex molecules 11 , there are only a handful of reports of directly using organosilanes for carboxylation reaction without involving any transition metal catalysts [19][20][21][22][23][24][25][26][27][28][29] . While organometallic reagent catalyzed carboxylation has already drawn extensive attention to radiochemistry research [30][31][32] , to the best of our knowledge, we have not found any reports of the use of the FMDS methodology for direct 11 Ccarboxylation. It is comprehensible that the high cost and necessity of stoichiometric amounts of organosilane reagents made this method less attractive in synthetic organic chemistry research when compared to other organometallic reagent catalyzed carboxylation methodologies 33,34 .…”
Section: Synthesis Of [ 11 C]acetoacetic Acid Via Fmds 11 C-carboxylamentioning
confidence: 98%
“…[2] On the other hand, radiolabelled compounds (containing tritium ( 3 H) or carbon-14 ( 14 C)) are still indispensable for investigating metabolic pathways and, more generally,t he in vivo fate of substances within absorption, distribution, metabolism, and excretion (ADME) studies.Over the last decade,important breakthroughs have been realized in the context of hydrogen isotope exchange (HIE), [3] which can be eyed as the most fundamental C À Hf unctionalisation process (Scheme 1). [4] Conceptually,t he development of as imilar approach to HIE for carbon isotopes,t hat is,c arbon isotope exchange (CIE), might be naturally considered as ac ornerstone for access to 13 C-and 14 C-labelled molecules in adirect and more sustainable way.H owever,t he development of selective catalytic CÀCbond activation processes has attracted less attention compared to CÀHa ctivation technologies. Using this well-established strategy,h ydrogen isotope incorporation is nowadays possible on multiple positions,which is an essential feature for the preparation of internal standards for MS,a nd with impressive degrees of selectivity even on molecules of high complexity,s uch as pharmaceuticals.…”
mentioning
confidence: 99%
“…[3] However, 3 H-labelled compounds may undergo undesirable in vivo metabolic degradation by enzymatic reactions and/or isotopic exchange with surrounding water, which can lead to 3 H-label loss.T his explains the complementary need for 14 Clabelled compounds.I ndeed, imbedding the 14 Ci sotope into the structural core of compounds is ah ighly recommended approach for tracing parent molecules and subsequent metabolites to elucidate their fate in vivo.N evertheless,t he preparation of 14 C-labelled molecules is often associated with high synthetic costs and the generation of significant amounts of radioactive intermediates and wastes,w hich need to be handled appropriately.T hese drawbacks are the result of the limited number of commercially available 14 Cs ources for its incorporation into substrates at an early stage of amulti-step radiosynthesis. [4] Conceptually,t he development of as imilar approach to HIE for carbon isotopes,t hat is,c arbon isotope exchange (CIE), might be naturally considered as ac ornerstone for access to 13 C-and 14 C-labelled molecules in adirect and more sustainable way.H owever,t he development of selective catalytic CÀCbond activation processes has attracted less attention compared to CÀHa ctivation technologies. This lag is mainly due to the higher inertness of C À C s-bonds compared to C À Hb onds.N onetheless,a fter significant progress in C À Cb ond activation with transition metals by oxidative addition over the last three decades, [5] thef irst examples of CIE have been recently described (Scheme 1).…”
mentioning
confidence: 99%
“…[4] Konzeptionell kçnnte die Entwicklung eines ähnlichen Ansatzes wie HIE fürK ohlenstoffisotope,a lso der Kohlenstoffisotopenaustausch (CIE), als Eckpfeiler füre inen direkten und nachhaltigeren Zugang zu 13 C-und 14 C-markierten Molekülen dienen. Dies erklärt den komplementären Bedarf an 14 C-markierten Verbindungen.…”
unclassified
“…Diese Nachteile resultieren daraus, dass die Anzahl kommerziell verfügbarer 14 C-Quellen, die in frühen Stadien einer mehrstufigen Radiosynthese in Substrate eingebaut werden kçnnen, begrenzt ist. [4] Konzeptionell kçnnte die Entwicklung eines ähnlichen Ansatzes wie HIE fürK ohlenstoffisotope,a lso der Kohlenstoffisotopenaustausch (CIE), als Eckpfeiler füre inen direkten und nachhaltigeren Zugang zu 13 C-und 14 C-markierten Molekülen dienen. Die Entwicklung selektiver katalytischer C-C-Bindungsaktivierungsprozesse hat jedoch im Vergleich zu C-H-Aktivierungstechniken weniger Aufmerksamkeit gefunden.…”
unclassified